Controllable growth of bulk cubic-phase CH3NH3PbI3 single crystal with exciting room-temperature stability. Issue 28 (10th June 2016) - Luan, Mengyu; Song, Junling; Wei, Xiangfeng; Chen, Fang; Liu, Jiehua
Abstract : Bulk cubic-phase CH3 NH3 PbI3 single crystal with exciting room-temperature stability was successfully synthesized in mixed-solvent method at 60 °C for the first time. Abstract : To obtain bulk cubic CH3 NH3 PbI3, chlorobenzene was employed to regulate the CH3 NH3 PbI3 γ-butyrolactone solution with high saturated solubility at room temperature and a high yield of crystal at 60 °C. As a result, bulk cubic CH3 NH3 PbI3 single crystal was successfully synthesized for the first time in mixed-solvent method at 60 °C, which is a little higher than the tetragonal–cubic phase inversion temperature.